Problem-Based Learning-Oriented Animated Learning Videos in Fifth-Grade Elementary School Science Content - Josapat Eleaser; I Made Tegeh; I Komang Sudarma (Jurnal Edutech Undiksha, 2023)
The lack of teacher ability to facilitate innovative learning media for students then impacts low student learning outcomes, so to overcome these problems, it is necessary to use innovative media in the learning process. This research aimed to describe the design and know the validity of problem-based learning-oriented animation videos in the science content of class V SD. This research belongs to the type of development research which was developed using the ADDIE model. The subjects involved in this study were educational technology experts, content experts, design experts, media experts, and trial students. Data collection in this study was carried out using the questionnaire method and the test method, with research instruments in the form of product validity sheets and tests of student learning outcomes. The data obtained in the study were then analyzed using qualitative descriptive analysis techniques, quantitative descriptive analysis, and t-test inferential statistical analysis. The results of the research analysis show that the review results of content experts are very well qualified (90.9%), design experts are very well qualified (92.3%), media experts are very well qualified (92.3%), individual test results are very well qualified (96.1%), and the results of the small group trials were very well qualified (91.4%). Based on these results, the animated video media developed are very good qualifications and can improve the learning outcomes of fifth-grade elementary school students.